"We Too Deserve a Place in the Sun": The Politics of Transvestite Identity in Weimar Germany - Sutton, Katie (German studies review, 2012)
Cross-dressing took on new political meanings in Germany's Weimar Republic, with the emergence of organizations and periodicals aimed at promoting the interests of self-identified "transvestites." This new sexological category, developed by Magnus Hirschfeld in 1910, formed the basis for a shared sense of identity and belonging among individuals who identified as members of the "opposite" sex. Drawing on the experiences of the homosexual emancipation movement and discourses of bourgeois respectability, middle-class transvestites came together to demand legal and social recognition, including acknowledgement of "transsexual" desires. Their efforts represent a critical but forgotten moment in the history of transgender political activism.